Occurrence of coenzyme F420 and its gamma-monoglutamyl derivative in nonmethanogenic archaebacteria. - Lin, X L (1986)
Analysis of the fluorescent compounds extracted from six different species of halobacteria and one species each of Sulfolobus and Thermoplasma revealed the universal occurrence of coenzyme F420, (N-[N-[O-[5-(8-hydroxy-5-deazaisoalloxazin-10-yl)-2,3,4-trihydroxy -4-pentoxyhydroxyphosphinyl]-L-lactyl]-L-gamma-glutamyl]-L -glutamic acid), or its gamma-monoglutamyl derivative or both. The total amount (approximately 100 pmol/mg [dry weight]) of these compounds found in the halobacteria studied was approximately 5% of the amount previously reported for methanogenic bacteria. The amount of F420 found in the Sulfolobus and Thermoplasma strains was approximately 1% of that found in the halobacteria. The major compound in all but one of the examined strains was the gamma-monoglutamyl derivative of F420; one strain of halobacteria contained only F420. For the halobacterium-derived samples, the additional glutamic acid was shown to be linked by a gamma-glutamyl peptide bond to the terminal glutamic acid of the F420 core structure by enzymatic hydrolysis of the samples with three different gamma-glutamyltranspeptidases. The product of this enzymatic hydrolysis was F420 with one less glutamic acid in the side chain.